Taxation of agricultural enterprises in Ukraine - Kostornoi, Serhii; Косторной, Сергій Володимирович; Косторной, Сергей Владимирович (Мелітополь: Видавничий будинок Мелітопольської міської друкарні, 2015)
Current changes in the tax system of agricultural enterprises are investigated. The sums of the fixed agricultural tax in 2014 and of the single tax in 2015 are compared. The directions for improvement of agricultural enterprises taxation are offered.
Keywords: agricultural enterprises taxation; fixed agricultural tax; single tax; VAT